Self-Service Laundry Booking Application for Tun Dr Ismail Residential College - NUR DINI SYAHIRA BT SERAJUDIN; A. MOSTAFA, SALAMA (Applied Information Technology And Computer Science, 2025)
The laundry booking application proposed in this project is intended to address the inconveniences associated with the laundry process in Tun Dr Ismail Residential College. The current laundry booking system, which operates on a "first come, first serve" model, often results in unpredictable wait times, user dissatisfaction, and expenditure of resources. A laundry booking application designed using object-oriented approach that modernizes the process, improves user convenience, and guarantees equitable access to laundry facilities are designed. This application has some great features like an that let students book laundry slots, checking machine availability in real-time, and notifications to let you know when student has booked a slot and when they’ve finished their cycle. Administrators have tools for monitoring laundry room usage and manage machine availability. As a result, the project offers a promising result that enhances functional effectiveness but also contributes to the overall satisfaction and well- being of the council community.